Analysis of The Effect of Using Fiber Aramid-Polyolefin on The Strength, Stiffness, and Durability of Warm Mix Asphalt - Christian Gerald Daniel (Institut Teknologi Bandung, 2020)
AbstractWarm asphalt technology is an alternative for road pavement structures. One method to improve the performance of warm mix asphalt is by using fiber as an additive. This study aimed to analyze the effect of using aramid and polyolefin fibers in warm mix asphalt through several tests, to provide recommendations for the optimum fiber content. 4-point bending and triaxial tests on the DAC-16 asphalt mix sample with a fiber proportion of 0.05% of the total sample weight resulted in an increase in fatigue life of 100% and a decrease in creep coefficient of 20%. Then, a tensile test was conducted on asphalt mortar sample, as well as semi circular bending test on DAC-16 asphalt mix sample, with three different fiber contents: 0.05%, 0.1% and 0.5%, and with two different fiber lengths: 19-mm and 38-mm. The test results showed an increase in stiffness up to 89% and a decrease in creep coefficient up to 45% compared to the control sample, also increased tensile strength by 12.5% and total energy by 17%. In addition, it was found that the addition of 38-mm fiber of 0.1% of the specimen's total weight gave optimum performance. It can be concluded that the addition of fiber with a length of 38-mm, a content of 0.1% gave an optimum mixture performance improvement. The CT scan result on the mortar sample explains the strengthening mechanism due to the addition of fiber, i.e. (i) load transfer between fibers and (ii) fiber-asphalt matrix interface bonding.Abstrak Teknologi aspal hangat menjadi salah satu alternatif untuk struktur perkerasan jalan. Salah satu metode untuk meningkatkan performa campuran aspal hangat yakni dengan menggunakan bahan tambah fibre. Penelitian ini hendak menganalisis pengaruh dari penggunaan fibre aramid dan polyolefin pada campuran aspal hangat melalui beberapa pengujian, untuk memberi rekomendasi dosis fibre yang optimum. Hasil uji 4-point bending dan triaxial pada sampel campuran aspal DAC-16 dengan proporsi fibre 0.05% berat sample total yakni peningkatan fatigue life sebesar 100% serta penurunan creep coefficient 20%. Kemudian, pengujian tarik dilakukan pada sampel aspal mortar, serta semi-circular bending test pada sample campuran aspal DAC-16, dengan tiga dosis fibre berbeda: 0.05%, 0.1% dan 0.5%, serta dengan dua panjang fibre yang berbeda: 19-mm dan 38-mm. Hasil pengujian menunjukkan peningkatan kekakuan hingga 89% serta creep coefficient yang menurun hingga 45% dibanding sample kontrol, juga peningkatan kuat tarik sebesar 12.5% dan total energi sebesar 17%. Selain itu, ditemukan bahwa penambahan fibre 38-mm sebanyak 0.1% dari total berat spesimen memberi performa optimum. Dapat disimpulkan bahwa penambahan fibre dengan panjang 38-mm, dosis 0.1% memberikan peningkatan performa campuran yang optimum. Hasil CT-Scan pada sampel mortar menjelaskan mekanisme perkuatan akibat penambahan fibre, yakni (i) transfer beban antar fibre dan (ii) interface bonding fibre-matriks aspal.